Impact of successive basketball matches in psychophysiological response and neuromuscular performance in adolescent players - de Lima Pinto, J. C. B.; Menezes, T. C. B.; Fonteles, A. I.; Mortatti, A. L. (Sport Sciences for Health, 2022)
Purpose This study aimed to analyze the impact of competition with successive basketball matches on mood, stress tolerance, competitive anxiety, total quality of recovery and neuromuscular performance in adolescent basketball athletes.